Analysis and Evaluation of E-Government Maturity in West Java Regional Devices Based on SPBE of Ministry of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia - Amalia, Endang; Rozahi Istambul, Muhammad; Supriyadi, IstambulHari; Hamdani, Dani; M. , Benny Chaniago (International Journal of Psychosocial Rehabilitation, 2020)
SPBE evaluation activities of these Government Agencies are formulated in such a way that they can be used as benchmarks to harmonize SPBE development programs and plans to produce integration, sustainability and quality of SPBE services. It is expected that all stakeholders involved in this evaluation can understand and follow the instructions set out in this book as well as possible so that the implementation of SPBE evaluations can run well and smoothly in accordance with the plans and schedules set.